Development of Sumberan Camping Ground Tourism in Improving Facilities in Lantan Village, Central Lombok - Darayani, Dhiafah Hera; Jihat, M; Cindrawati, Cindrawati; Ahmad, Mahli; Sakaki, Muhammad; Sarmila, Sarmila (Abdi Masyarakat, 2023)
One of the problems that exist in the Lantan Village Tourism area, North Batukliang District, Central Lombok Region, specifically in the Sumberan Camping Ground tourist area, is the lack of awareness of the potential around them which they might be able to use as additional resources to be useful for developing tourism in their area. One of the programs implemented in the Sumberan Camping Ground Area is repairing the gate at the Sumberan Camping Ground, repairing the ITC sign, installing paranet around the pool at the Sumberan Camping Ground, making signs that must be adhered to, and installing lighting in the Sumberan Camping Ground area. The objectives of this work program are: 1) To create comfort for visitors who come to the Sumberan Camping Ground; 2) To create quality, characterful, creative, and innovative Human Resources; 3) To encourage and motivate children or youth to be enthusiastic about learning and always maintain the sustainability of tourism in Lantan Village. The result of this work program is that the community is enthusiastic about participating in these activities. Apart from that, this work program also aims to preserve tourism in Lantan Village, specifically at the Sumberan Camping Ground.